The genome sequence of the long-horned flat-body, Carcina quercana (Fabricius, 1775) [version 1; peer review: 2 approved] - David Lees; Douglas Boyes (Wellcome Open Research, 2023)
We present a genome assembly from an individual male Carcina quercana (the long-horned flat-body; Arthropoda; Insecta; Lepidoptera; Depressariidae). The genome sequence is 409 megabases in span. Most of the assembly (99.96%) is scaffolded into 30 chromosomal pseudomolecules, including the assembled Z sex chromosome. The complete mitochondrial genome was also assembled and is 15.3 kilobases in length. Gene annotation of this assembly on Ensembl identified 18,108 protein coding genes.